Implementation of the Partnership System in Improvement Competitiveness of Cooperative Business in Pasir Jambu Village, Pasir Jambu District, Bandung Regency - Hamdan Azhar Siregar; Otom Mustomi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cooperatives in Indonesia through a partnership system are felt to be increasingly urgent to implement if it is considered that the indications of the country's economy are not yet optimal. Because it has not been maximized, it is very important to immediately improve the business climate in order to create a conducive and healthy economic climate. The problems in this research are, How is the implementation of partnerships in increasing the competitiveness of cooperative businesses, especially in Pasirjambu village, Pasirjambu district, Bandung district. What factors hinder the development of cooperatives in Pasirjambu village, Pasirjambu district, Bandung, while the purpose of this study is to know and analyze how the implementation of the partnership system in increasing the competitiveness of cooperative businesses, especially in Pasirjambu village, Pasirjambu district, Bandung district. In this study, the method used was the empirical normative legal research method, namely research conducted by conducting secondary research first and then proceeding with conducting research on primary data in the field. Results and discussion the creation of such an economic climate allows economic activity to develop. Evenly, both investment activities, production and distribution activities as well as other economic activities. The role of the law is very important to create certainty in the legal relationship of the parties who enter into a partnership, therefore the law must be able to encourage and be able to provide legal certainty in increasing competitiveness. In increasing competitiveness in the form of partnerships without a definite rule of law, the relationship between the two parties suffers from setbacks and uncertainty. Conclusion The perspective of partnership implementation, based on legal aspects that can provide justice, with the aim of empowering small businesses, cooperatives in nation building, namely equitable development, employment and business opportunities, income distribution, and increasing business capacity, increasing competitiveness, increasing exports, equitable ownership business and strengthen the structure of the national economy. Through the national business partnership movement, all development actors will jointly renew their determination to mobilize all potentials and strengths to accelerate the rate of growth of the just Indonesian nation.